Perkembangan Kerajaan Matan Pada Masa Gusti Muhammad Saunan (Tahun 1922-1942) Ketapang Kalimantan Barat - Rifaldi*, Muhamad; Firmansyah, Haris; Putri, Astrini Eka (Universitas Syiah Kuala, 2024)
This research aims to find out the history of various periods in several different periods in the Matan Ketapang Kingdom, West Kalimantan, especially in the period 1922-1942, this is an effort to pass on memories to the next generation. This research method itself uses historical research which consists of Topic Selection, Heuristics, Verification, Interpretation, and Historiography. Heuristics or source collection in this research uses oral sources and secondary sources in the form of books related to the Matan Kingdom, both the history of the founding of the Matan Kingdom and how the Matan Kingdom moved from its previous location. Then in the results of this research it was discovered how the arrival of the Dutch and Japanese made people's lives very miserable, where they lived with burdensome